FLYPAPER EFFECT ATAS DANA ALOKASI UMUM DAN PENDAPATAN ASLI DAERAH TERHADAP BELANJA MODAL KABUPATEN/KOTA DI PROVINSI MALUKU UTARA - Karwur, Jesiska C; Ilat, Ventje; Warongan, Jessy D.L (Universitas Sam Ratulangi, 2018)
This research is aimed examine whether the General Allocation Fund and Regional Real Income effect the Capital Expenditure Regrency/City in the Province of North Maluku and to analyze the possibility of the accurrence of flypaper effect to the Capital Expenditure of Regrency/City in the Province of North Maluku in 2014-2016. The Population of this research is report on realization of regional budjet and expenditure budjet (APBD) Regrency/City in the area of North Maluku Province. This sample use with method pusposive sampling and the number of samples are 30 data. The data that was used are secondary datas which has been obtained from the report on realization of regional budjet and expenditure budjet (APBD) Regrency/City in the Province of North Maluku from 2014 to 2016 which have been obtained from Badan Pusat Statistik (BPS) Maluku Utara. The data analysis instrument that was use in this research is the multiple linear analysis. The results shows that : 1) The General Allocation Fund has significant influence to the Capital Expenditure Regrency /City in the Province of North Maluku. 2) The Regional Real Income fund has no significant influence to the Capital Expenditure Regrency/City in the Province of North Maluku. 3) The flypaper effect has occurred on capital expenditure of Regrency/City in the Province of North Maluku.Keywords: General Allocation Fund (DAU), Regional Real Income (PAD), flypaper effect